Factors Affecting the Occurrence of Cost Overrun Based on Relative Importance Index (RII) on Toll Road Projects - Magdalena, Sara; Citra, Zel (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
In the implementation of a construction project, it is not uncommon for many obstacles to arise during its continuity, resulting in one of the common impacts, namely cost overrun. Referring to some of the problems that arise, it is calculated that there is a cost overrun of around 30% of the initial value. This research uses quantitative research methods by collecting data and distributing questionnaires. After that, some data was tested with the help of SPSS and the analysis method, namely the Relative Importance Index, to process the data. Based on the analysis carried out, the top 5 (five) rankings were obtained sequentially related to the occurrence of cost overrun in construction projects, namely frequent delays in work with an RII score of 0,8, incomplete/inappropriate information, and data provided with a score of 0,7, slow arrival of materials during implementation with a score of 0,689, improper project scheduling with a score of 0,689, and high frequency of equipment repair with a score of 0,611, as for the control measures that can be concluded, including making written records or records of events and things that cause these factors, communicating to the employer along with the consequences that can occur, and several other control measures according to the factors faced. From the study's results, it can be concluded that this research is something new and can be beneficial and used primarily by contractors to understand and find the right solutions for toll road project work and develop for other projects that experience cost overrun.